2021
DOI: 10.3390/microorganisms9010175
|View full text |Cite
|
Sign up to set email alerts
|

Self-Crossing Leads to Weak Co-Variation of the Bacterial and Fungal Communities in the Rice Rhizosphere

Abstract: The rhizomicrobial community is influenced by plant genotype. However, the potential differences in the co-assembly of bacterial and fungal communities between parental lines and different generations of rice progenies have not been examined. Here we compared the bacterial and fungal communities in the rhizomicrobiomes of female parent Oryza rufipogon wild rice; male parent Oryza sativa cultivated rice; their F1 progeny; and the F2, F3 and F4 self-crossing generations. Our results showed that the bacterial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Domestication has been shown to alter the diversity of microbes in the rhizosphere of crops such as corn [45], tomato [46], wheat [47], and rice [48,49]. Chang et al [50] compared the bacterial communities of wild and domesticated rice genotypes and found that Frankiaceae was enriched in the rhizosphere of cultivated Oryza sativa but absent from the rhizosphere of wild Oryza rufipogon. This result highlights that unique microbes that are not recruited by wild relatives are enriched in the rhizosphere of domesticated cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestication has been shown to alter the diversity of microbes in the rhizosphere of crops such as corn [45], tomato [46], wheat [47], and rice [48,49]. Chang et al [50] compared the bacterial communities of wild and domesticated rice genotypes and found that Frankiaceae was enriched in the rhizosphere of cultivated Oryza sativa but absent from the rhizosphere of wild Oryza rufipogon. This result highlights that unique microbes that are not recruited by wild relatives are enriched in the rhizosphere of domesticated cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Soil pH and electrical conductivity (EC) were measured in a suspension of soil in water at a ratio of 1:2.5 (w/v). Soil total nitrogen (TN), soil organic matter (SOM), available phosphorus (AP), and available potassium (AK) were measured by the Kjeldahl method, potassium dichromate volumetric method, NaHCO 3 extraction method and ammonium acetate extraction method, respectively, as described by Chang et al [50].…”
Section: Analysis Of Rhizosphere Soil Physical and Chemical Propertiesmentioning
confidence: 99%
“…8). Members of Xanthobacteraceae have been found to associate with the rhizosphere and roots of rice (Chang et al 2021) and tea plantations (Chen et al 2021). In addition, bacteria within the families Rhizobiaceae, Comamonadaceae, and Xanthobacteraceae have been closely linked to N cycling processes including N-fixation, nitrification, and denitrification in the past studies (Chen and Ni 2011;Gomez-Alvarez et al 2014;Jang et al 2020), which might help explain the soil N dynamics of the gravel pit.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study showed that self-cross of rice ( Oryza sp.) decreased the differences in rhizosphere bacterial and fungal communities between parental lines and progeny generations ( Chang et al, 2021 ). So, it is necessary to combine traditional plant cross-breeding with soil microbiomes ( Nerva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%